PENGARUH MODAL USAHA, LOKASI USAHA DAN PENGGUNAAN ECOMMERCETERHADAP PENJUALAN UMKM BIDANG FASHION DI DENPASAR - Putri, Ni Kadek Ayu Adistha Widiani; Purwanti, Putu Ayu Pramitha (E-Jurnal Manajemen, 2022)
This study aims to analyze the influence of business capital, business location, and E-commerce simultaneously and partially on the sales of MSMEs in the fashion sector in Denpasar City. Research sampling was carried out using the accidental proportional sampling method. Based on the calculation results, the number of samples used in this study totals a total of 100 samples that will be included in the business category that is in the selected regional cluster and the business category that is outside the cluster. The analysis techniques used are simultaneous multiple linear boundary tests and partial regression coefficient significance tests tested using the SPSS 25.0 program. The results showed that business capital, business location, and the use of E-commerce simultaneously had a positive effect on the sales of MSMEs in the fashion sector in Denpasar City. The results of this study also show that business capital, business location, and the use of E-commerce partially have a positive effect on the sales of MSMEs in the fashion sector in Denpasar City. Keywords: Venture capital; business location; E-commerce; sales; Fashion